2012
DOI: 10.1002/eat.22053
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interventions in the eating disorders: What is the evidence?

Abstract: The widespread interest in using motivational approaches in the eating disorders is not strongly supported by the literature. The current evidence base does not support the widespread dissemination of motivation-enhancing interventions in the eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 34 publications
4
71
0
3
Order By: Relevance
“…Motivational Interviewing is an established practice model, with mounting evidence in research for its effective improvement of psychosocial risks, especially mental health (Brody, 2009;Westra, 2004;Zerler, 2009), substance abuse (Gingerich & Peterson, 2013;Johnson, Sacks, & Edmonds, 2010;Simpson & Zuckoff, 2011;Westra, Aviram, & Odell, 2011), alcohol abuse (Branscum & Sharma, 2010;Feldstein & Forcehimes, 2007;Harris, Aldea, & Kirkley, 2006;Martens, Smith, & Murphy, 2013), and eating disorders (Knowles, Anokhina, & Serpell, 2013;Macdonald, Hibbs, Corfield, & Treasure, 2012;Weiss, Mills, Westra, & Carter, 2013). Gingerich and Peterson (2013) found that MI is also cost-effective, requires fewer therapeutic sessions, and is adaptable to a variety of environments more so than other intervention solutions.…”
Section: Motivational Interviewing (Mi)mentioning
confidence: 99%
“…Motivational Interviewing is an established practice model, with mounting evidence in research for its effective improvement of psychosocial risks, especially mental health (Brody, 2009;Westra, 2004;Zerler, 2009), substance abuse (Gingerich & Peterson, 2013;Johnson, Sacks, & Edmonds, 2010;Simpson & Zuckoff, 2011;Westra, Aviram, & Odell, 2011), alcohol abuse (Branscum & Sharma, 2010;Feldstein & Forcehimes, 2007;Harris, Aldea, & Kirkley, 2006;Martens, Smith, & Murphy, 2013), and eating disorders (Knowles, Anokhina, & Serpell, 2013;Macdonald, Hibbs, Corfield, & Treasure, 2012;Weiss, Mills, Westra, & Carter, 2013). Gingerich and Peterson (2013) found that MI is also cost-effective, requires fewer therapeutic sessions, and is adaptable to a variety of environments more so than other intervention solutions.…”
Section: Motivational Interviewing (Mi)mentioning
confidence: 99%
“…These results extend upon the extant literature by identifying a mechanism through which EA may promote better treatment response. Research on enhancing motivation for recovery to date has found mixed and inconsistent support for interventions that focus solely on explicit motivation [2]. It is possible that modifying underlying psychological processes (such as EA) could subsequently enhance motivation for change, and perhaps more consistently so.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that this resistance is partially attributable to characteristically high ambivalence toward recovery and low motivation to abstain from disordered eating behaviors among patients [2, 3]. Higher levels of motivation are linked to more favorable treatment response [4], even among patients who have a longer duration of illness [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 There is also some evidence that motivational-enhancement approaches (including internet-delivered programs) can increase motivation to change and improve ED symptomatology, [3][4][5][6][7][8] although more research is needed to identify the optimum strategies for enhancing motivation for recovery. 9,10 Fundamental to this research endeavor has been the development of several instruments for assessing motivation to change and related constructs (e.g., decisional balance) in the context of EDs. 11 However, most of these measures have been developed in English-speaking populations and all have been developed in Western countries.…”
Section: Introductionmentioning
confidence: 99%